Iowa Birdline update, August 8, 1994 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1994)
Email of the Iowa Birdline update for August 8, 1994. Highlights of the update include a second state record of a Black-headed Gull as well as sightings of Burrowing Owls, Barn Owls, a Laughing Gull, a Snowy Egret, and the continued presence of the Pacific Loon. Also included are handwritten notes for the next week's update with sightings of a Eurasian Tree Sparrow and several species of shorebirds. Epson - sheet feed/flatbed